Occurence and inheritance of 2n pollen in Musa - Ortíz, R. (Oxford University Press, 1997)
Sexual polyploidization explains the formation of most polyploid crop species and provides means for their genetic improvement. This paper reports the occurrence and inheritance of 2 n pollen in diploid and polyploid Musa . Pollen samples of male fertile accessions available in the field gene bank of the International Institute of Tropical Agriculture were microscopically examined throughout a calendar year. Based on pollen diameter 2 n pollen producers were identified. The presence of 2 n pollen in diploid species suggests that unilateral sexual polyploidization (2 n×n ) could have been involved in the origin of triploid Musa species. Segregation data suggests that at least one dominant gene controls 2 n pollen production in Musa . Further introgression of desirable alleles from diploid species to polyploids could be achieved either through unilateral or bilateral (2 n×2n ) sexual polyploidization in Musa .